The book of time (Westbridge Books, 1980)
In this large and accurately researched book, seven writers offer guided tours of different aspects of time. The pace is frequently too fast and the landscape too crowded for the fullest edification and enjoyment: thus the opening piece, Roy Porter's "The History of Time", starts by whizzing past Donne (on the left) and Neanderthal man (on the right), plunging into forests of historical and literary erudition which do little more than establish that a lot of people have thought a lot of different things about time. The conclusion is that "Time has ceased to be cyclical, and become development" (i.e., the turning wheel of the seasons is less important in modern thought than the arrow of entropy). To this, Porter darkly adds: "We are all children of Time. We must not forget that Time devours her own children." Note the pronoun: obviously old man Chronos has at last slipped with his scythe...